Multimodal meaning making: Navigational acts in online speaking tasks. (November 2018) - Knight, Janine; Dooly, Melinda; Barberà, Elena
Abstract: Intentionally clicking screen-based navigational resources can be one way in which learners exercise agency in online tasks by making choices and acting on them. Because such navigational acts require learners to be initiators and responders of navigational resources, possibilities may exist for meaning making beyond the lingual. However, the meaning making potential of navigational resources and the impact on task processes have received little attention in Second Language Acquisition research. This case study explored how learners across three peer-to-peer, online spoken interaction tasks carried out navigational acts using an audioconferencing tool. The analysis employed Multimodal (inter)actional analysis, a Computer Mediated Discourse analytical perspective and incorporated learners' explicit mention of resources on the screen in order to 'track' their trajectories during task process. Results suggest that depending on different case trajectories, learners orally negotiated navigational acts as part of meta-modal talk, or navigated in ways whereby this oral negotiation was eliminated from talk in the target language. Furthermore, technological tool-use was also negotiated physically, underscoring the importance of learner roles as tool users or managers and the non-verbal meaning making emerging from this process. Implications for task design and language learning in online spoken interaction tasks are discussed.